Case study : the experience of managers : the how of organisational learning after patient incidents in a hospital - Mok, Yin Shan Joyce (Massey University, 2009)
This case study describes the learning capability of a hospital after patient incidents. The theoretical framework is based on Carroll, Rudolph and Hatakenaka’s model of four stages of organisational learning. Ten managers were interviewed and documents such as incident management policy, quality plans and incident reports were examined. The ten participants include five clinical managers who are responsible for investigating incidents and five unit managers who are responsible for signing off incident reports. This study found that incident investigations generated valuable learning for the participants. Being the learning agent, they also appeared to influence and lead team learning and, to some extent, organisational learning. Most of the participants appeared to be practising between the constrained stage and the open stage of learning. This study uncovers the concepts of preparedness, perception and persistence. The application of these exemplary concepts has strengthened the learning capability of some participants and distinguishes them as practising at the open stage of learning. By employing these concepts, The Hospital can also gain leverage to progress from the constrained stage to the open stage of learning that supports a systems approach, advocates double-loop learning and facilitates the culture of safety. This case study has found that The Hospital assumes a controlling-orientation to ensure staff’s compliance with policies and procedures to prevent patient incidents. However, it also advocates a safety culture and attempts to promote learning from patient incidents. This impetus is inhibited by the obstacles in its incident management system, the weak iii modes of transfer of learning and hindering organisational practices. Three propositions are offered to overcome these barriers. Firstly, revolutionise the incident management system to remove obstacles due to the rigid format of Incident Forms, the difficulty in retrieving information and the lack of feedback. Secondly, provide regular, safe, transparent and egalitarian forums for all staff to learn from patient incidents. Facilitated incident meetings have been shown to be more effective platforms for learning than a bureaucratic approach via policies, procedures, training and directive decisions delivered during departmental meetings or by written communications. Thirdly, attain a balance between controlling and learning to mitigate the effects of bureaucratic process and the silo phenomenon.
Keywords: Organisational learning; Organisational procedures; Incident management; Hospital management; Fields of Research::350000 Commerce, Management, Tourism and Services::350200 Business and Management